Adverse effects of anti-tuberculosis drugs on HepG2 cell bioenergetics. (June 2017) - Elmorsy, E; Attalla, SM; Fikry, E; Kocon, A; Turner, R; Christie, D; Warren, A; Nwidu, LL; Carter, WG
Tuberculosis (TB) is an intractable chronic infection. Disease treatment with anti-TB drugs remains challenging due to drug-induced hepatotoxicity. The toxicity of the anti-TB drugs rifampicin (RIF), isoniazid (INH) and pyrazinamide (PZA) either alone or in combination was investigated in HepG2 cells. Assays of intracellular adenosine triphosphate (ATP) levels at 4-, 24- and 48-h post-exposure to gradient concentrations of RIF, INH and PZA were conducted. Drug-induced effects on mitochondrial membrane potential (MMP), mitochondrial complex I and complex III activity, nicotinamide adenine dinucleotide (NAD + ) levels and cellular lactate production were assessed. Decreased ATP levels were dose-dependent and correlated with drug exposure duration. Approximate 24-h IC50 s were 0.5 mM, 70 mM and 84 mM for RIF, INH and PZA, respectively. Twenty-four hours post-drug treatment, reductions of MMP ( p = 0.0005), mitochondrial complex I and III activities ( p = 0.0001 and p = 0.0003, respectively), NAD + levels ( p = 0.0057) and increased lactate production ( p < 0.0001) were observed. Drug combinations used to mimic cumulative drug treatments induced a synergistic inhibition of mitochondrial complex I activity. An assessment of cellular ultrastructure using transmission electron microscopy indicated drug-induced mitophagy. Collectively, our study suggests that hepatotoxicity of commonly employed anti-TB drugs is mediated by their curtailment of mitochondrial function.